In Memoriam Vera Vesković-Vangeli: In Memoriam Вера Весковиќ-Вангели - Milevska, Suzana; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Suzana Milevska | Сузана Милевска Title (English): In Memoriam Vera Vesković-Vangeli Title (Macedonian): In Memoriam Вера Весковиќ-Вангели Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 11-12 Page Count: 2 Citation (English): Suzana Milevska, “In Memoriam Vera Vesković-Vangeli,” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 11-12. Citation (Macedonian): Сузана Милевска, „In Memoriam Вера Весковиќ-Вангели“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 11-12.